Endophytic bacteria of Catharanthus roseus as an alternative source of vindoline and application of response surface methodology to enhance its production - Anjum, Nawed; Chandra, Ramesh (Archives of Biological Sciences, 2019)
The requirement for novel, cost-effective pharmaceutical compounds is growing. We screened endophytic bacteria of Catharanthus roseus for the production of vinca alkaloids. Vindoline-producing endophytic bacteria was identified as Microbacterium sp. Vindoline was purified and characterized using column chromatography, TLC, HPLC and electrospray ionization mass spectrometry. The subsequent aim of this study was to design a cost-efficient media that can maximize vindoline production from Microbacterium sp. Initial optimization of the nutritional requirement and of the process parameters were carried out by monothetic analysis. Key factors obtained were optimized by the central composite design of response surface methodology. This model was also validated by repeating the experiment under the optimized conditions, which resulted in maximum production of 82 μg/L (predicted response was 76.21 μg/L). Reliability of the experiments was confirmed by ANOVA analysis, regression coefficient, prediction vs actual chart and a 3D response plot, which determined the fit of the model. This study should serve as a reference point for the use of statistical techniques in bacterial systems for production of bioactive, anticancer compounds by plant endophytes. https://doi.org/10.2298/ABS180802044A Received: August 2, 2018; Revised: September 19, 2018; Accepted: September 20, 2018; Published online: October 2, 2018 How to cite this article: Anjum N, Chandra R. Endophytic bacteria of Catharanthus roseus as an alternative source of Vindoline and application of response surface methodology to enhance its production. Arch Biol Sci. 2019;71(1):27-38.